1988
DOI: 10.1007/bf01216704
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cytology of ganglion neurons and satellite glial cells in the superior cervical ganglion of the sheep. Relationship with ganglion neuron size

Abstract: Neurons and glial cells of the superior cervical ganglion of sheep were investigated with morphometric methods in the light and electron microscope. The nerve cell sectional area (measured on nucleated cell profiles) ranged from 165 to 2500 microns2, which corresponds to range in cell diameter from 14 to 56 microns and a range in cell volume from 1600 to 93,000 microns3, i.e. a 60-fold volume difference between smallest and largest neurons. The distribution of cell sizes appeared unimodal, with a predominance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
6
19
1
2
Order By: Relevance
“…The microstructural arrangement of the dog's CMG was similar between adult and middle-aged dogs, e.g., the CMG was divided into distinct compartments by capsular septa of connective tissue as reported for mammalian prevertebral ganglia by Gabella et al (1988), Szurszewski and King (1989), Banks (1992), Szurszewski and Miller (1994), Miolan and Niel (1996), Schmidt (1996), and Gagliardo et al (2003). In pups, however, two or four ganglion masses were noticed and they were structurally linked by connective tissue and each one was ensheathed by a ganglion capsule.…”
Section: Morphological Aspects: Macro-and Microstructuresupporting
confidence: 59%
“…The microstructural arrangement of the dog's CMG was similar between adult and middle-aged dogs, e.g., the CMG was divided into distinct compartments by capsular septa of connective tissue as reported for mammalian prevertebral ganglia by Gabella et al (1988), Szurszewski and King (1989), Banks (1992), Szurszewski and Miller (1994), Miolan and Niel (1996), Schmidt (1996), and Gagliardo et al (2003). In pups, however, two or four ganglion masses were noticed and they were structurally linked by connective tissue and each one was ensheathed by a ganglion capsule.…”
Section: Morphological Aspects: Macro-and Microstructuresupporting
confidence: 59%
“…For example, SCG neurons that innervate the SMG were shown to be significantly greater in number and size than those that innervate the iris [49]. Soma of sympathetic neurons innervating larger targets are reported to be larger than those that innervate smaller targets, and the animals with larger body weight have larger SCG neurons than those with smaller body weight [18,42]. Indeed, it was suggested that the terminal arborizations of axons of ganglionic neurons are more extensive in larger animals, and in those larger animals they comprise a larger number of neurons, larger neuronal soma and more arborized nerve terminals [38,42].…”
Section: Introductionmentioning
confidence: 99%
“…The SCG is divided into distinct compartments by capsular septa of connective tissue as reported for mammalian sympathetic ganglia (Fioretto et al, 2007;Gabella et al, 1988;Miolan and Niel, 1996;Ribeiro et al, 2004;Schmidt, 1996;Szurszewski and King, 1989;Szurszewski and Miller, 1994). In addition, Gabella (1976) postulated that the capsule of connective tissue which surrounds the ganglia of the sympathetic trunk is continuous with the epineurium of the associated nerves.…”
Section: B978mentioning
confidence: 94%